Loss of PINK1 increases the heart's vulnerability to ischemia-reperfusion injury. - Hilary K Siddall; Derek M Yellon; Sang-Bing Ong; Uma A Mukherjee; Niall Burke; Andrew R Hall; Plamena R Angelova; Marthe H R Ludtmann; Emma Deas; Sean M Davidson; Mihaela M Mocanu; Derek J Hausenloy (PLoS ONE)
Objectives Mutations in PTEN inducible kinase-1 (PINK1) induce mitochondrial dysfunction in dopaminergic neurons resulting in an inherited form of Parkinson's disease. Although PINK1 is present in the heart its exact role there is unclear. We hypothesized that PINK1 protects the heart against acute ischemia reperfusion injury (IRI) by preventing mitochondrial dysfunction. Methods and results Over-expressing PINK1 in HL-1 cardiac cells reduced cell death following simulated IRI (29.2±5.2% PINK1 versus 49.0±2.4% control; N = 320 cells/group P<0.05), and delayed the onset of mitochondrial permeability transition pore (MPTP) opening (by 1.3 fold; P<0.05). Hearts excised from PINK1+/+, PINK1+/- and PINK1-/- mice were subjected to 35 minutes regional ischemia followed by 30 minutes reperfusion. Interestingly, myocardial infarct size was increased in PINK1-/- hearts compared to PINK1+/+ hearts with an intermediate infarct size in PINK1+/- hearts (25.1±2.0% PINK1+/+, 38.9±3.4% PINK1+/- versus 51.5±4.3% PINK1-/- hearts; N>5 animals/group; P<0.05). Cardiomyocytes isolated from PINK1-/- hearts had a lower resting mitochondrial membrane potential, had inhibited mitochondrial respiration, generated more oxidative stress during simulated IRI, and underwent rigor contracture more rapidly in response to an uncoupler when compared to PINK1+/+ cells suggesting mitochondrial dysfunction in hearts deficient in PINK1. Conclusions We show that the loss of PINK1 increases the heart's vulnerability to ischemia-reperfusion injury. This may be due, in part, to increased mitochondrial dysfunction. These findings implicate PINK1 as a novel target for cardioprotection.